Public Confidence and Willingness to Report Crimes in Nigeria: The Submission of the Residents of Abeokuta South Local Government - Ogunmefun Folorunsho Muyideen; Onyeukwu Bruno Chibike (Randwick International of Social Science Journal, 2026)
Evidence gathered from several cases against the performance of the police shows that security work cannot be done effectively by the police without the community members. The community’s willingness to report incidents of antisocial behaviour to the police gives room for effective and efficient performance of the Nigeria police. The collective responsibility between the community members and the police will helps the police to discharge and carry out their primary, legal and modern functions. In Nigeria, several publications have linked the poor performance of the Nigeria Police to different internal and external factors. However, this paper intends to examine the willingness of the residents of Abeokuta South Local Government to report crime to the Nigeria Police as expected. Extant literature were reviewed while instinctual drive theory was adopted for the explanation of the research inquiry. The study adopted Mixed (quantitative and qualitative) methods and cross sectional survey for the collection of data from 256 residents of Abeokuta South Local Government area in seven (7) wards. Multistage was adopted to break the study locations from wards to streets and house numbers before purposive sampling method was adopted for the administration of face to face questionnaire to respondents. The Linear Regression analysis was adopted and the study found out that trust in police fairness (0.152, p=005), openness in engagement (0.200, p=<005), trust in police procedure (0.172, p=<005), rights protection (0.138, p=<005) and institutional commitment (0.127,p=005) were significant compared to other variables stated. The qualitative results corroborate scholarly submissions of the past indicating that lack of confidence and willingness to report crime stem from the corrupt nature of the Nigeria Police and poor response to emergencies.